Implant placement with guided bone regeneration in esthetic zone- A case report - Maharjan, A; Joshi, S; Verma, A; Gorkhali, RS (Journal of Nepalese Prosthodontic Society, 2021)
Alveolar ridge deficiency is considered a major limitation for successful implant placement, as well as for the long-term success rate, especially in the anterior maxillary region. Implants placed without regard for prosthetic position often results in dental restorations that are functionally and esthetically compromised. Adequate peri-implant bone support is essential for immediate and long-term implant stability, as well as for future esthetic outcome. To achieve this goal, augmentation of lost bone is often necessary. A variety of surgical approaches have been proposed to enhance the alveolar bone volume. Guided bone regeneration (GBR) is the most common technique for localized bone augmentation. GBR, by application of cell occlusive membranes that mechanically exclude non-osteogenic cell populations from the surrounding soft tissues, has become a well-documented and highly successful procedure for localized augmentation of the atrophic jaw before or simultaneously with implant placement. This case report presents simultaneous approach of guided bone regeneration and implant placement in the maxillary anterior region with narrow ridge defect.